Odpowiedź:
zad 9
a)
6x(2x - 1) + 4x(4 - 3x) = 12x² - 6x + 16x - 12x² = 10x = 10 * (- 4,2) = - 42
b)
(y - 2)(y + 3) - y² = y² - 2y + 3y - 6 - y² = y - 6 = - 1 1/7 - 6 = - 7 1/7
c)
a(a + b) - 2a² = a² + ab - 2a² = - a² + ab = - 5² + 5 * (- 3) = - 25 - 15 = - 40
d)
m(2m + 6) - 3( 1 + 2m) = 2m² + 6m - 3 - 6m = 2m² - 3 = 2 * (1/n)² - 3 =
= 2 * 1/(- 5)² - 3 = 2 * (1/25) - 3 = 2/25 - 3 = 2/25 - 2 25/25 = - 2 23/25
zad 10
a) (2x + 4)/2 = 2(x + 2)/2 = x + 2
b) 2 * (6x - 18)/12 = 2 * 6(x - 3)/12 = 2 * (x - 3)/2 = x - 3
c) 4 * (x - 7)/2 - 6 * (3 - x)/3 = 2(x - 7) - 2(3 - x) = 2x - 14 - 6 + 2x = 4x - 20
d) - (6a + 4)/2 - (9a - 3).3 = - 2(3a + 2)/2 - 3(3a - 1)/3 = - (3a + 2) - (3a - 1) =
= - 3a - 2 - 3a + 1 = - 6a - 1